First Total Syntheses of Tetracenomycins C and X. Issue 41 (30th August 2017) - Sato, Shogo; Sakata, Keiichiro; Hashimoto, Yoshimitsu; Takikawa, Hiroshi; Suzuki, Keisuke
Abstract: The first total syntheses of tetracenomycins C and X were achieved, featuring 1) preparation of a hexasubstituted naphthonitrile oxide by successive benzyne cycloadditions and an oxidative ring‐opening reaction; 2) a novel ortho ‐quinone mono‐acetal as the A‐ring unit; 3) construction of three contiguous stereogenic centers by an asymmetric benzoin cyclization, an isoxazole oxidation, and a stereoselective reduction. Abstract : Tetracenomycins C and X were prepared by total syntheses, which featured, hexasubstituted naphthonitrile oxide and ortho ‐quinone mono‐acetal intermediates, construction of three contiguous stereogenic centers by an asymmetric benzoin cyclization, an isoxazole oxidation, and a stereoselective reduction.